Penanaman Nilai Kejujuran melalui Kantin Kejujuran di Taman Kanak-kanak - Tabi'in, As'adut; Nurlela, Nurlela (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Honesty is a character that everyone should have. However, the character of honesty is deteriorating every day. Therefore, cultivating honesty values should start from an early age so that it becomes a habit and character. This study aims to describe the cultivation of honesty value through the honesty canteen at the Islamic Integrated Kindergarten of Cahaya Sunnah, Sei. Bangkar, Seberida Subdistrict, Indragiri Hulu Regency. This research uses a descriptive-qualitative approach. The data were collected using observation, in-depth interviews, and documentation techniques. The informants in this study consisted of the principal, 3 teachers, and 35 students. The collected data were analyzed in three stages, namely data reduction, data display, and then verification and conclusion. The results of this study show that the cultivation of honesty values through the honesty canteen is carried out in several stages, namely planning, implementation, organization, monitoring, and evaluation. In this way, children are accustomed to being honest, trained to maintain cleanliness, to be responsible, to be disciplined, to obey the rules, to be independent, and to be patient.